The Influence of Work Compensation and Flexibility on Job Satisfaction Case Study on Online Ojek Drivers in Bandar Lampung - Fikry Afriyanda; Habibullah Jimad (International Journal of Regional Innovation, 2023)
In the current era of technological development, several technological developments have emerged in the field of transportation, such as online transportation. It is not surprising that there are many start-ups or companies engaged in online transportation. This development creates an application model that can be accessed via mobile phones. The large number of online-based transportation service provider companies makes competition even tougher, so companies must improve the performance of online partners or drivers. For this reason, the performance of online drivers is an important concern for every online transportation company to be able to win the competition. This study aims to determine the effect of compensation and flexibility on job satisfaction of online motorcycle taxi drivers in Bandar Lampung. The research method used is quantitative, namely a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. In this study using a questionnaire with a Likert scale. The population of this study were online motorcycle taxi drivers in Bandar Lampung and 189 people were taken as a sample. Data analysis used multiple linear regression analysis with the IBM SPSS 26 analysis tool. The results showed that compensation and flexibility have a positive effect on job satisfaction. Companies that provide online transportation services are expected to be able to increase compensation such as salaries, benefits, incentives or performance bonuses and provide flexibility in time and place of work that can be adjusted by online motorcycle taxi drivers. So that with that the job satisfaction of online motorcycle taxi drivers will increase.